Strategi Pengelolaan Badan Usaha Milik Desa (Bumdes) Di Desa Maccini Baji Kecamatan Bajeng Kabupaten Gowa - Fitrianita, Nabila; Setiawati, Budi; Mone, Ansyari (Universitas Muhammadiyah Makassar, 2022)
This study purposed to find out the Management Strategy of Village Owned Enterprises (BUMDes) in Maccini Baji Village, Bajeng District, Gowa Regency. This study used descriptive qualitative, data sources were primary data and secondary data. The results of the study showed that the strategy for managing village-owned enterprises had 4 aspects that affect the management strategy, namely the planning aspect had followed the procedures listed in the AD/ART, the organizing aspect was appointing a manager who was an element of the village community and did not have duties in the village government, the directive aspect had supervised the work of members as well as monitoring and evaluating aspects of managers conducting evaluations every 3 months, 6 months and annually. Then the factors that influenced the management of village-owned enterprises in Maccini Baji village were the existence of a system of cooperation to full support by the village government, equity and procurement of bumdes business funds. Keywords: Strategy, Management and Village Owned Enterprises (BUMDes).